PENGEMASAN PAKET WISATA CITY TOUR BERBASIS BUDAYA DI KOTA DENPASAR BALI - Mulyana, Hadi; Nurhayati, Ainun; Meisya Auliyaa, Dwi; Ramdhani, Fauzi; Valencia, Regina (JURNAL MEKAR, 2025)
Denpasar City has a lot of cultural tourism potential such as historical buildings, arts, traditional markets and community culture. Therefore, this potential can be developed into a city tour package in Denpasar. This study aims to determine the potential of cultural tourism in Denpasar and how to package culture-based city tour packages. This research uses data collection techniques such as observation, interviews and literature review. The results show that the main tourism potential in Denpasar is the charm of temples and shrines, traditional markets and museums. This potential is then packaged into four tour packages, namely Melali ke Puri, Heritage Denpasar City Tour, Beautiful Cultural of Denpasar City Tour, and Historic Denpasar City Tour. In the packaging of these tour packages, information is provided in the form of narratives, tables and graphs. In this way, culture-based city tour packages in Denpasar can attract tourists.